Incidence and predictors of restenosis after coronary stenting in 10 004 patients with surveillance angiography - Cassese, Salvatore; Byrne, Robert A.; Tada, Tomohisa; Pinieck, Susanne; Joner, Michael; Ibrahim, Tareq; King, Lamin A.; Fusaro, Massimiliano; Laugwitz, Karl-Ludwig; Kastrati, Adnan (Heart, 2014)
Objective Systematic investigation of restenosis after percutaneous coronary intervention (PCI) with bare metal stents (BMS) or first or second generation drug eluting stents (DES) in large scale, broadly inclusive patient populations undergoing follow-up angiography represents a gap in our scientific knowledge. We investigated the incidence of angiographically proven restenosis and its predictors in patients undergoing PCI with stents. Methods All patients undergoing successful implantation of coronary stents for de novo lesions from 1998 to 2009 and follow-up angiography at 6-8 months at two centres in Munich, Germany were eligible for inclusion. Patients with cardiogenic shock, dialysis dependent renal insufficiency or previous cardiac transplantation were excluded. Data were prospectively collected. The incidence of restenosis, defined as diameter stenosis ≥50% in the in-segment area at follow-up angiography, and its predictors were evaluated. Results A total of 12 094 patients met inclusion criteria. Angiographic follow-up was available for 10 004 patients (77.5%) with 15 004 treated lesions. Binary restenosis was detected in 2643 (26.4%) patients. Use of first generation DES versus BMS (OR 0.35, 95% CI 0.31 to 0.39) and second generation DES versus first generation DES (OR 0.67, 95% CI 0.58 to 0.77) were independent predictors of lower rates of restenosis. At multivariate analysis, smaller vessel size (OR 1.59, 95% CI 1.52 to 1.68, for each 0.5 mm decrease), total stented length (OR 1.27, 95% CI 1.21 to 1.33, for each 10 mm increase), complex lesion morphology (OR 1.35, 95% 1.21 to 1.51), presence of diabetes mellitus (OR 1.32, 95% 1.19 to 1.46), and history of bypass surgery (OR 1.38, 95% CI 1.20 to 1.58) were independently associated with restenosis and were similar across the spectrum of stent devices. Conclusions In this large cohort of patients with angiographic surveillance we demonstrated the impact of device development on antirestenotic efficacy, with sequentially improved efficacy from BMS to first generation DES to second generation DES. Predictors of restenosis were small vessel size, increased stented length, complex lesion morphology, diabetes mellitus, and prior bypass surgery.
CRIS-Team Scopus Importer:2023-03-08